PCSK9 in Myocardial Infarction and Cardioprotection: Importance of Lipid Metabolism and Inflammation - Andreadou, Ioanna; Tsoumani, Maria; Vilahur, Gemma; Ikonomidis, Ignatios; Badimon, Lina; Varga, Zoltán V.; Ferdinandy, Péter; Schulz, Rainer (Frontiers in Physiology, 2020)
Extensive evidence from epidemiologic, genetic, and clinical intervention studies has indisputably shown that elevated low-density lipoprotein cholesterol (LDL-C) concentrations play a central role in the pathophysiology of atherosclerotic cardiovascular disease. Apart from LDL-C, also triglycerides independently modulate cardiovascular risk. Reduction of proprotein convertase subtilisin/kexin type 9 (PCSK9) has emerged as a therapeutic target for reducing plasma LDL-C, but it is also associated with a reduction in triglyceride levels potentially through modulation of the expression of free fatty acid transporters. Preclinical data indicate that PCSK9 is up-regulated in the ischaemic heart and decreasing PCSK9 expression impacts on infarct size, post infarct inflammation and remodeling as well as cardiac dysfunction following ischaemia/reperfusion. Clinical data support that notion in that PCSK9 inhibition is associated with reductions in the incidence of myocardial infarction, stroke, and coronary revascularization and an improvement of endothelial function in subjects with increased cardiovascular risk. The aim of the current review is to summarize the current knowledge on the importance of free fatty acid metabolism on myocardial ischaemia /reperfusion injury and to provide an update on recent evidence on the role of hyperlipidemia and PCSK9 in myocardial infarction and cardioprotection.